Analisis Komparatif Pemenuhan Aspek Responsif, Komunikatif, dan Edukatif PPID BPS, Kemendikbud Ristek RI dan KESDM RI Menggunakan Bonferroni – ANOVA Post Hoc Test - Bunga Mardhotillah; Zurweni Zurweni; Cut Multahadah; Corry Sormin; Fernando Mersa Putra (Departement of Mathematics Education, 2024)
As part of good government governance, transparency, Accountability and participation are non-negotiable principles in management government. Good Governance can be realized if government institutions have it good transparency and accountability. Openness of public information aims to realizing good governance, so that the public can actively participate in controlling it every policy step taken by the government. As a Public Agency, PPID Ministry ESDM is obliged to provide and publish public information, provide information to the public or applicants for public information that is accurate, true and not misleading and in a simple way. On the other hand, the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) continues to strive to improve program performance and policies in the fields of education, culture, research and technology. One of them is by improving service excellence (service excellence) which is oriented towards stakeholders. Indications of the success of the Ministry of Education and Culture's programs and policies are wrong the other is satisfaction from stakeholders in the form of a stakeholder index score satisfaction. To measure the level of customer satisfaction, a survey is needed national level which is carried out in a sustainable manner. In the bureaucratic reform program The Ministry of Education and Culture has determined eight program areas of change to focus on bureaucratic reform within the Ministry of Education and Culture, namely, 1) Change Management; 2) Strengthening Supervision; 3) Strengthening Performance Accountability; 4) Institutional Strengthening; 5) Strengthening Management; 6) Strengthening the HR Management System for Apparatus; 7) Reinforcement Legislation; 8) Improving the Quality of Public Services consisting of: (a) Student Services; (b) Education Unit Services; (c) Educational Substance Services; (d) Teacher and Education Services; (e) Cultural Services; (f) Available Language Services supported by optimization through improving the performance of the Ministry of Education and Culture's PPID in sector/subsector. The BPS RI is the main reference that can be accessed by the public related to Indonesian data and statistics, optimizing the role of PPID in its agencies by issued PPID BPS Decree NUMBER: B-323/02400/HK.200/07/2022 concerning Public Information Service Standards In BPS Environment. This research aims to carry out a Multiple Comparisons of Fulfillment of Responsive, Communicative and Educative Aspects of PPID BPS, Ministry of Education and Culture, Research and Technology of the Republic of Indonesia and Ministry of Energy and Mineral Resources of the Republic of Indonesia Using Bonferroni – ANOVA Post Hoc Test.